2017
DOI: 10.1088/1742-6596/884/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of theobromine 200 mg/l topical gel exposure duration against surface enamel hardness resistance from 1% citric acid

Abstract: Abstract. Theobromine can be used to prevent the demineralization of enamel and can stimulate the growth of new enamels. This study analyzes the effect of theobromine's gel duration exposure on enamel hardness resistance from 1% citric acid. Twenty-eight specimens were divided into three experimental groups; were exposed to theobromine gel 200 mg/l for 16, 48, and 96 minutes; and were then immersed in 1% citric acid. The control group was only immersed in 1% citric acid. Results: A Wilcoxon test showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…Our results stated that although theobromine gel caused an increase in the Ca/P ratio but didn't reach the level of the control group. This coincides with Herisa et al 2017 [48] who showed that theobromine enhanced the hardness of enamel surface after demineralization but did not restore it to its initial hardness.…”
Section: Benferroni Post-hoc Test For Pairs Comparisonssupporting
confidence: 90%
“…Our results stated that although theobromine gel caused an increase in the Ca/P ratio but didn't reach the level of the control group. This coincides with Herisa et al 2017 [48] who showed that theobromine enhanced the hardness of enamel surface after demineralization but did not restore it to its initial hardness.…”
Section: Benferroni Post-hoc Test For Pairs Comparisonssupporting
confidence: 90%
“…Theobromine fluid increased the Ca/P ratio, according to our findings, but not to the same extent as the control group This coincides with Irawan et al2017's findings that theobromine improved enamel surface hardness after demineralization but did not restore it to its original hardness [16] .…”
Section: Discussionsupporting
confidence: 89%
“…For many years, fluoride's caries-preventive actions were attributed primarily to a decrease the enamel solubility. [15,16] Fluoridation methods used in the community, such as water and salt fluoridation, are significant in the prevention of dental cavities. Salt fluoridation is proposed as an alternate community option when water fluoridation is not possible.…”
Section: Fluoridementioning
confidence: 99%
“…Struktur email gigi desidui mengandung lebih banyak komponen organik bila dibandingkan mineral anorganik hidroksiapatit, dan tidak tahan terhadap asam 1,2 . Hal ini menyebabkan gigi desidui mudah mengalami kerusakan, sehingga diperlukan suatu upaya pencegahan untuk mempertahankan gigi desidui 3,4 .…”
Section: Pendahuluanunclassified